Pengaruh Kombinasi Pupuk Kandang Kambing Dan Urea Terhadap Pertumbuhan Dan Hasil Tanaman Selada Merah (Lactuca sativa L.) Varietas Red Rapid - Aulia Kamila; Sulistyo Sidik Purnomo; Rommy Andhika Laksono (Peneliti.net, 2021)
Red lettuce is one of the most consumed vegetables and one of the important commodities supporting the global economy. In 2019 there was a decline due to the lack of soil fertility. Therefore, the provision of organic and inorganic fertilizers can be done or can be an alternative solution to the problem of infertile soil. The purpose of this study was to obtain the right combination dose of goat manure and urea on the growth and yield of red lettuce (Lactuca sativa L.) red rapid varieties. The experiment was carried out from June to July 2021. The experiment was carried out in the new land of Singaperbangsa Karawang University located in Pasirjengkol Village, Majalaya District, Karawang Regency. The research method used a Randomized Block Design (RAK) consisting of 5 treatments with 5 replications, namely A (control), B (goat manure 20 tons/ha and urea 150 kg/ha), C (goat manure 20 tons/ha and urea 300 kg/ha), D (goat manure 30 tons/ha and urea 150 kg/ha), and E (goat manure 30 tons/ha and urea 300 kg/ha). Data were analyzed using analysis of variance and further test with Duncan's multiple distance test at 5% level. The experimental results showed that there was a significantly different effect of the combination dose of goat manure and urea on fresh weight per plot of red lettuce (Lactuca sativa L.) red rapid varieties. Treatment D (goat manure 30 tons/ha and urea 150 kg/ha) was able to provide the highest growth and yield red lettuce parameters for plant height, number of leaves per plant, leaf area per plant, fresh weight per plant, and fresh weight per plot.